Sensorless Control of a Fault-Tolerant Multi-Level PMSM Drive - Kamel Saleh; Mark Sumner (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper presents a new technique to track the saliency position in a permanent magnet synchronous motor (PMSM) post a single phase open-circuit fault. The PMSM is driven by a fault-tolerant multi-level inverter that is utilized to implement a fault-tolerant control strategy to minimize system performance degradation post the fault.The fault-tolerant multi-level inverter is consisting of a number of insulated-gate bipolar transistors (IGBTs). The dynamic current reponses of the PMSM motor due to the switching actions of these IGBTs are used extract the saliency position. This process is not introducing any modification to the operation of the fault-tolerant multil-level inverter as it uses only the fundamental pulse width modulation (PWM) waveform. Moreover,it considers the modifications introduced to the PMSM motor and the multi-level inverter post the fault.Simulation results are provided to verify the eﬀectiveness of the proposed strategy of saliency tracking of a PMSM motor driven by a fault-tolerant four-leg multi-level inverter over a wide range of speeds in the case of a single-phase open circuit fault.